Relationship between overweight and obesity and insufficient micronutrient intake: a nationwide study in Taiwan. (14th April 2023) - Lin, Shih-Pi; Fang, Hsin-Yu; Li, Ming-Chieh
Abstract: The aim of the present study is to examine whether overweight or obese people in Taiwan have an inadequate intake of selected micronutrients. A population-based study was conducted using data from the Nutrition and Health Survey in Taiwan (NAHSIT) 2013–2016. We evaluated fourteen nutrient intakes using the 24 h dietary recall method. The dietary reference intake (DRI) adherence was estimated by the prevalence of participants whose intake was lower than the recommended dietary allowance (RDA) or adequate intakes (AIs) for selected micronutrients. Body mass index (BMI) ≥ 27 kg/m 2 and waist circumference (WC), with men having WC ≥ 90 cm or women having WC ≥ 80 cm, were defined as obesity. A total of 3075 participants aged 19 years and above were included. After adjusting for confounders, we found that obese women have a lower DRI adherence of vitamin C (odds ratio (OR) 0⋅73, 95 % confidence interval (CI) 0⋅56, 0⋅95) and magnesium (OR 0⋅72, 95 % CI 0⋅54, 0⋅95), compared with normal-weight women. Obese men have a higher DRI adherence of vitamin B3 (OR 1⋅70, 95 % CI 1⋅29, 2⋅23), iron (OR 1⋅46, 95 % CI 1⋅06, 2⋅00) and zinc (OR 1⋅41, 95 % CI 1⋅07, 1⋅85), compared with normal-weight men. Similar findings were found using WC to define obesity. We conclude that obese women may have insufficient intakes of vitamin A, vitamin C and magnesium.